2022
DOI: 10.1101/2022.08.10.503449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Doublecortin and JIP3 are neural-specific counteracting regulators of dynein-mediated retrograde trafficking

Abstract: Mutations in the microtubule (MT)-binding protein doublecortin (DCX) or in the MT-based molecular motor dynein result in lissencephaly. However, a functional link between DCX and dynein has not been defined. Here, we demonstrate that DCX negatively regulates dynein-mediated retrograde transport by reducing dynein's association with MTs and by disrupting the composition of the dynein motor complex. Previous work showed an increased binding of the adaptor protein C-Jun-amino-terminal kinase-interacting protein 3… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 113 publications
(190 reference statements)
2
2
1
Order By: Relevance
“…One possible explanation is that previous work did not use polarity-marked microtubules (Sun et al, 2011; Watt et al, 2015); thus, it is possible that the motility they detected was in fact minus-end-directed and dynein-driven. Based upon our data, and consistent with the recent reports on the activation of dynein by JIP3 (Rao et al, 2022; Singh et al, 2022) we conclude that JIP3 and JIP4 robustly activate dynein motility, with only marginal activation of kinesin under the conditions tested. Consistent with these observations, labeled JIP3 and JIP4 both move almost exclusively retrograde in neuronal axons (Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…One possible explanation is that previous work did not use polarity-marked microtubules (Sun et al, 2011; Watt et al, 2015); thus, it is possible that the motility they detected was in fact minus-end-directed and dynein-driven. Based upon our data, and consistent with the recent reports on the activation of dynein by JIP3 (Rao et al, 2022; Singh et al, 2022) we conclude that JIP3 and JIP4 robustly activate dynein motility, with only marginal activation of kinesin under the conditions tested. Consistent with these observations, labeled JIP3 and JIP4 both move almost exclusively retrograde in neuronal axons (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Concurrent with our study, two other groups have shown that purified recombinant truncated JIP3 is sufficient to activate dynein-mediated motility in vitro (Rao et al, 2022; Singh et al, 2022). Our study adds to this growing body of work, as the approaches used here (1) include endogenous binding partners, which negates the need to use truncated constructs; (2) is performed at physiological temperature on dynamically growing microtubules; and (3) includes competing kinesin complexes.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations